Analgesic effects of GpTx-1, PF-04856264 and CNV1014802 in a mouse model of NaV1.7-Mediated pain - Deuis, Jennifer R.; Wingerd, Joshua S.; Winter, Zoltan; Durek, Thomas; Dekan, Zoltan; Sousa, Silmara R.; Zimmermann, Katharina; Hoffmann, Tal; Weidner, Christian; Nassar, Mohammed A.; Alewood, Paul F.; Lewis, Richard J.; et al. (Toxins, 2016)
Loss-of-function mutations of NaV1.7 lead to congenital insensitivity to pain, a rare condition resulting in individuals who are otherwise normal except for the inability to sense pain, making pharmacological inhibition of NaV1.7 a promising therapeutic strategy for the treatment of pain. We characterized a novel mouse model of NaV1.7-mediated pain based on intraplantar injection of the scorpion toxin OD1, which is suitable for rapid in vivo profiling of NaV1.7 inhibitors. Intraplantar injection of OD1 caused spontaneous pain behaviors, which were reversed by co-injection with NaV1.7 inhibitors and significantly reduced in NaV1.7−/− mice. To validate the use of the model for profiling NaV1.7 inhibitors, we determined the NaV selectivity and tested the efficacy of the reported NaV1.7 inhibitors GpTx-1, PF-04856264 and CNV1014802 (raxatrigine). GpTx-1 selectively inhibited NaV1.7 and was effective when co-administered with OD1, but lacked efficacy when delivered systemically. PF-04856264 state-dependently and selectively inhibited NaV1.7 and significantly reduced OD1-induced spontaneous pain when delivered locally and systemically. CNV1014802 state-dependently, but non-selectively, inhibited NaV channels and was only effective in the OD1 model when delivered systemically. Our novel model of NaV1.7-mediated pain based on intraplantar injection of OD1 is thus suitable for the rapid in vivo characterization of the analgesic efficacy of NaV1.7 inhibitors.<br
Keywords: OD1; NaV1.7; PF-04856264; CNV1014802; raxatrigine; GpTx-1; pain